Health system governance for injury care in low- and middle-income countries: a survey of policymakers and policy implementors - Alice Sitch; Justine Davies; Kathryn Chu; Stephen Tabiri; Junaid Razzak; Lucia D’Ambruoso; Alemayehu Amberbir; Abebe Bekele; Agnieszka Ignatowicz; Mohammed Bukari; Derbew Fikadu Berhe; Barnabas Alayande; et al. (BMJ Global Health)
Introduction Good health system governance is essential for reducing high mortality and morbidity after injury in low- and middle-income countries (LMICs). Unfortunately, the current state of governance for injury care is not known. This study evaluated governance for injury care in Ghana, Pakistan, Rwanda and South Africa, four LMICs with diverse contexts, to allow understanding of similarities or difference in the status of governance systems in different LMICs.Method This cross-sectional study captured the perceptions of 220 respondents (31 policymakers and 189 policy implementers) on injury care governance using the framework for governance in health system developed by Siddiqi. Input was captured in 10 domains: strategic vision; participation and consensus; rule of law; transparency; responsiveness; equity and inclusion; effectiveness and efficiency; accountability; intelligence and information; and ethics.Result The median injury care governance score across all domains and countries was 29% (IQR 17–43). The highest median score was achieved in the rule of law (50, 33–67), and the lowest scores were seen in the transparency (0, 0–33), accountability (0, 0–33), and participation and consensus (0, 0–33) domains. Median scores were higher for policymakers (33, 27–48) than for policy implementers (27, 17–42), but the difference was not statistically significant.Conclusion The four studied countries have developed some of the foundations of good injury care governance, although many governance domains require more attention. The gap in awareness between policymakers and policy implementers might reflect a delayed or partial implementation of policies or lack of communication between sectors. Ensuring equitable access to injury care across LMICs requires investment in all domains of good injury care governance.